2016
DOI: 10.1377/hlthaff.2016.0839
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Dental Sealant Programs Prevent Cavities And Are Cost-Effective

Abstract: Untreated cavities can have far-reaching negative consequences for people’s ability to eat, speak, and learn. By adolescence, 27 percent of low-income children in the United States will have untreated cavities. School-based sealant programs typically provide dental sealants (a protective coating that adheres to the surface of molars) at little or no cost to students attending schools in areas with low socioeconomic status. These programs have been shown to increase the number of students receiving sealants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 24 publications
7
61
0
Order By: Relevance
“…Hence, community‐based interventions such as school‐based sealant programs could be a cost‐saving approach for this population (Griffin et al. ), although that would depend on the relative effectiveness of sealants applied in school‐based settings compared with dental office settings. Access to care also could be potentially improved by increasing dentist participation by raising Medicaid reimbursement rates (Beazoglou et al.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, community‐based interventions such as school‐based sealant programs could be a cost‐saving approach for this population (Griffin et al. ), although that would depend on the relative effectiveness of sealants applied in school‐based settings compared with dental office settings. Access to care also could be potentially improved by increasing dentist participation by raising Medicaid reimbursement rates (Beazoglou et al.…”
Section: Resultsmentioning
confidence: 99%
“…The 34 articles identified correspond to 33 studies, because one study was reported in more than one article. Finally, 33 complete economic evaluations were included for data extraction and analysis …”
Section: Resultsmentioning
confidence: 99%
“…The United States Community Preventive Services Task Force recommends sealants as the primary preventive method for caries programs [18,19]. Overall, dental sealant programs prevent subsequent tooth fillings and were found to be cost-effective [19].…”
Section: Discussionmentioning
confidence: 99%